2017
DOI: 10.1007/s40261-017-0572-6
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Polymorphisms of SLCO1B1, CYP2E1 and UGT1A1 and Susceptibility to Anti-Tuberculosis Drug-Induced Hepatotoxicity: A Chinese Population-Based Prospective Case–Control Study

Abstract: Genetic polymorphisms of SLCO1B1 and UGT1A1 were found to be associated with susceptibility to ATDH. Molecular identification of susceptibility genes provides a theoretical foundation for predicting the likelihood of ATDH and predicting treatment outcomes in tuberculosis patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
29
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(32 citation statements)
references
References 29 publications
0
29
0
Order By: Relevance
“…Elevated ALT levels might indicate a higher risk of hepatotoxicity [ 30 ]. It was reported that SLCO1B1 genetic variants are associated with drug-induced hepatotoxicity [ 31 , 32 ].…”
Section: Discussionmentioning
confidence: 99%
“…Elevated ALT levels might indicate a higher risk of hepatotoxicity [ 30 ]. It was reported that SLCO1B1 genetic variants are associated with drug-induced hepatotoxicity [ 31 , 32 ].…”
Section: Discussionmentioning
confidence: 99%
“…The sample size calculation of this protocol was based on studies of genetic analyses of ATDH. In previous studies, the sample sizes used have been relatively small (ranging from 846 to 46147), which makes it difficult to achieve an adequate statistical power. Furthermore, too small a sample size to detect true evidence for an association increases false negative rates and reduces the reliability of a study,48 which is one of the reasons for heterogeneity of results between different studies.…”
Section: Discussionmentioning
confidence: 99%
“…Organic anion‐transporting polypeptide (OATP) 1B1 is one of the most important drug transporters that mediates the hepatic uptake of many endogenous and xenobiotic compounds . OATP1B1 is encoded by gene of SLCO1B1 on chromosome 12p and expressed on the basolateral membrane of human hepatocytes . Numerous genetic variants have been identified in the SLCO1B1 gene, especially the non‐synonymous SNPs, such as rs4149056 (c.521T > C) in exon 5 and rs2306283 (c.388A > G) in exon 4, which has been found to alter the activity of OATP1B1 both in vitro and in vivo .…”
Section: Discussionmentioning
confidence: 99%
“…Previously, a Chinese population‐based study found that the UGT1A1*27 and UGT1A1*28 were associated with an increased risk of anti‐tuberculosis‐induced hepatotoxicity (ATDH) . In addition, Sun et al found that UGT1A1*6 (rs4148323) significantly reduced the risk of ATDH. However, in our study, we found that UGT1A1*6 (rs4148323) was associated with a significantly increased risk of MMI‐DILI before Bonferroni correction.…”
Section: Discussionmentioning
confidence: 99%